2015
DOI: 10.2147/tcrm.s89816
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management of hemophilia patients receiving total hip and knee arthroplasty: a complication report of two cases

Abstract: It has been recognized that perioperative hemostasis management after joint-replacement surgery for hemophilia patients is complicated and cumbersome, due to the necessity of rigorous monitoring for clotting-factor levels throughout the infusion. Between 2005 and 2014, we examined seven patients with hemophilia A (ten joints: six hips and four knees) receiving total hip or knee arthroplasty (THA or TKA) for hemophilic arthropathy. One male patient (31 years old) showed an intra-articular hematoma formation aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Another suitable study was found, giving us a final yield of 20 articles. 8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Figure 1 outlines the literature search process.…”
Section: Databases Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another suitable study was found, giving us a final yield of 20 articles. 8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Figure 1 outlines the literature search process.…”
Section: Databases Search Resultsmentioning
confidence: 99%
“…Haemostatic control is maintained by monitoring clotting-factor levels through continuous factor infusion. 8 This systematic review aims to examine the current literature regarding THA in haemophilic patients with the objective of determining clinical outcomes and complication rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efek puncak faktor VIII harus diperhatikan untuk memastikan kesesuaian jumlah faktor VIII yang akan diinfuskan dan interval pemberian dosis. [6][7][8] Induksi anestesi harus dilakukan dengan perlahan dan obat-obatan seperti suksinilkolin dihindari untuk mencegah guncangan atau kontraksi pada otot, yang dapat memperburuk keadaan hemoragik pada otot dan persendian. [9][10] Penggunaan infus perifer umumnya cenderung tidak mengalami pendarahan berlebihan.…”
Section: Pembahasanunclassified
“…4 TKA in haemophiliacs is a technically challenging procedure due to the presence of anatomical deformities, arthrofibrosis and poor bone quality. 5 The perioperative course is further complicated by the need for monitored therapy of the underlying coagulation disorder, 6 while still allowing early postoperative rehabilitation. 7 Despite this, TKA has been shown to achieve excellent outcomes in this patient group, with significant improvement in pain scores, flexion contractures, range of movement and functional scores.…”
Section: Introductionmentioning
confidence: 99%